New soil composition data for Europe and Australia: Demonstrating comparability, identifying continental-scale processes and learning lessons for global geochemical mapping - Reimann, Clemens; de Caritat, Patrice (The Science of the total environment, 2012)
New geochemical data from two continental-scale soil surveys in Europe and Australia are compared. Internal project standards were exchanged to assess comparability of analytical results. The total concentration of 26 oxides/elements (Al2O3, As, Ba, CaO, Ce, Co, Cr, Fe2O3, Ga, K2O, MgO, MnO, Na2O, Nb, Ni, P2O5, Pb, Rb, SiO2, Sr, Th, TiO2, V, Y, Zn, and Zr), Loss On Ignition (LOI) and pH are demonstrated to be comparable. Additionally, directly comparable data for 14 elements in an aqua regia extraction (Ag, As, Bi, Cd, Ce, Co, Cs, Cu, Fe, La, Li, Mn, Mo, and Pb) are provided for both continents. Median soil compositions are close, though generally Australian soils are depleted in all elements with the exception of SiO2 and Zr. This is interpreted to reflect the generally longer and, in places, more intense weathering in Australia. Calculation of the Chemical Index of Alteration (CIA) gives a median value of 72% for Australia compared to 60% for Europe. Element concentrations vary over 3 (and up to 5) orders of magnitude. Several elements (total As and Ni; aqua regia As, Co, Bi, Li, Pb) have a lower element concentration by a factor of 2–3 in the soils of northern Europe compared to southern Europe. The break in concentration coincides with the maximum extent of the last glaciation. The younger soils of northern Europe are more similar to the Australian soils than the older soils from southern Europe. In Australia, the central region with especially high SiO2 concentrations is commonly depleted in many elements. The new data define the natural background variation for two continents on both hemispheres based on real data. Judging from the experience of these two continental surveys, it can be concluded that analytical quality is the key requirement for the success of global geochemical mapping. ► New continental-scale soil geochemistry data are provided for Australia and Europe. ► Procedures to guarantee comparability of the datasets are demonstrated. ► Element concentrations show 3 to 5 orders of magnitude variation on both continents. ► The data provided define the soil geochemical background at the continental scale. ► Tight analytical quality control is a key requirement for global geochemical mapping.